ASPEK HUKUM LEMBAGA JAMINAN BANK GARANSI LEGAL ASPECTS OF BANK GUARANTEE SECURITY AGENCY - Lily Erlianti (Journal of Law ( Jurnal Ilmu Hukum ), 2013)
Bank guarantee is one of the banking products aimed at providing facilities in the form of guarantees (individual) to the community in developing its business.  Bank guarantees that are form of forbearance is a facility provided by the bank as a public service function using bank services that support its business activities.  If the party is assured of default occurs, the bank will comply, so that the receiving party may submit claim guarantee to the bank.The bank guarantee can be given a variety of purposes, namely: (1) for the delivery of goods either financed or not financed with bank loans, (2) to obtain Customs Revenue Information (KPP) on goods that L/C have been paid in full by importer, (3) for the expenditure items that L/C was not been paid in full by importer; (4) a bank guarantee for bid construction projects; 5) to carry out development projects in accordance with the provisions that have been agreed upon between the assured, (6) for protect or provide compensation for execution of the work of a liability in a particular position and (7) for the purpose of paying the down payment.In connection with the legal aspects, the bank guarantee must be stated clearly and should not be presupposed, in the sense that bank as a guarantor must be stated that the bank will act as guarantors of the secured party.